Comparative Study of Platelet count and C-Reactive Protein among Gram Positive, Gram Negative and Fungal Sepsis in Newborns - Rabindran, Rabindran; Parakh, Hemant; JK, Ramesh; Reddy, Prashant (International Journal of Medical Research and Review, 2015)
Introduction: Septicemia is characterized by positive blood culture, thrombocytopenia & elevated C-reactive protein. Objective: To compare platelet indices and CRP among gram-positive, gram negative and fungal sepsis in newborns. Methods: This is a retrospective case analysis of 52 blood culture positive patients between January-2012 to December-2014. The parameters examined were Baseline Platelet Count, Change In Platelet Count, (Baseline Platelet count- Change in Platelet count)/ Baseline Platelet Count , Platelet nadir, incidence, duration & severity of Thrombocytopenia, baseline CRP, change in CRP, (baseline CRP- change in CRP)/ baseline CRP, CRP peak, incidence & duration of raised crp. Statistical analysis: All data were collected in validated preformatted proforma sheet & analysed using appropriate statistical methods. Results: Majority (61.53%) had gram negative sepsis. Klebsiella was the commonest organism & was isolated in 21.15% of babies. Weight of the baby (p= 0.014), CRP Peak (p= 0.034), incidence of high CRP (p = 0.003), duration of high CRP (p= 0.004) & duration of thrombocytopenia (p = 0.001) differed significantly among gram-positive, gram negative & fungal sepsis. Conclusion: We noted higher rise in CRP with prolonged duration following Gram negative sepsis. However the incidence of both raised CRP and thrombocytopenia were more among fungal sepsis. Though the onset was delayed, lower platelet nadir, more severe thrombocytopenia with prolonged duration was noted among fungal sepsis.